The Management of Student Care Systems According to the Four Brahmavihra Principles in Schools Under the MahaSarakham Secondary Educational Service Area Office - Thipkrathok, Udomsak; Kangpheng, Samrit; Chotivungso, PhrakhruPaladBoonchuay (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to: 1. study the state of managing student care systems according to the Four Brahmavihra Principles in schools under the Maha Sarakham Secondary Educational Service Area Office; 2. explore guidelines for managing student care systems according to the Four Brahmavihra Principles in schools under the same office. The study used a mixed-methods approach, combining qualitative and quantitative research. The research instruments included a questionnaire and an interview. The target group consisted of 327 school administrators and teachers, selected using the Taro Yamane formula with a 0.05 error margin. Data analysis for the quantitative aspect used descriptive statistics, including percentage, mean, and standard deviation, with the questionnaire having a reliability coefficient of 0.98. The research results were as follows: 1. The state of managing student care systems according to the Four Brahmavihra Principles in schools under the Maha Sarakham Secondary Educational Service Area Office, was generally at a high level. The areas with the highest to lowest levels of practice were: Mett (Loving-Kindness), Upekkh (Equanimity), Mudit (Sympathetic Joy), and Karu (Compassion). 2. The guidelines for managing student care systems according to the Four Brahmavihra Principles in schools under the Maha Sarakham Secondary Educational Service Area Office, include Mett: screen and gather student information confidentially, showing close care and attention without neglecting problems that could affect society; Karu: organize parent-teacher meetings, build a parent network, and work together to provide student support, fostering a sense of security for parents; Mudit: recognize and commend students for good behavior and achievements, encouraging them to take pride in their talents and interests; Upekkh: record screening processes and student information, separate students with issues into groups for tailored support, and identify the root causes of problems to find appropriate solutions.